Rēzekne Jewish Cemetery as a Representative Substructure of the “Other” in the Culture of Latgale - Olga Senkāne (Acta Humanitarica Academiae Saulensis)
The aim of this study is to analyze the verbal and non-verbal signs of the Rēzekne Jewish cemetery with the cultural semiotic approach and to find out the hybridization features of the Jewish semiosphere in Latgale. The article describes the Rēzekne Jewish cemetery as a representative substructure of the “other” in the culture of Latgale with special traditions of language and ritual graphics, valuable genealogical material and historical evidence about the fate of local Jews and with a special tomb cult, determined by the ethnically diverse environment.